Machine Learning and Weighted Gene Coexpression Network–Based Identification of Biomarkers Predicting Immune Profiling and Drug Resistance in Lung Adenocarcinoma - Tian Zhang; Han Zhou (International Journal of Genomics)
Conclusion: This study may provide a theoretical reference for future exploration of potential diagnostic and prognostic biomarkers for LUAD.